(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
The study involved the monitoring of a clinical case by a behavior-analysis therapist and it identified, classified and analyzed the basic functions of the therapists verbalizations and analyzed the verbalizations of both therapist and client with regard to established relationships between clients responses and prior or subsequent environmental events. The analysis of the therapists verbalizations was based on categories related to the basic functions of the therapists verbalization which were also analyzed together with the clients verbalizations based on the categories of analysis, which were stipulated if the interlocutor established relationships between the clients response and prior or subsequent events. The analysis of the results showed that the therapist did not present a standardized model for interventions. What prevailed were interventions of an investigative nature and those in which he confronted the client with issues which she herself had previously mentioned. Only a small portion of the therapists interventions suggests links between the response of the client and environmental contingencies. Among the latter, the antecedentresponse connections were predominant. Compared to the therapist, the client established a greater number of relationships between environmental events and her responses, which were also of the antecedent-response type.